The Germany’s policy of regulating labour migration - Vashko, Irina M.; Kemnitz, Alexander (Journal of the Belarusian State University. International Relations, 2018)
The present article is dedicated to the analysis of the conceptual aspects of Germany’s labour market integration policy for immigrants. The conclusion is made that differences in the right to access to work for various categories of immigrants and different skills and opportunities for migrants in Germany led to differences in their economic integration. The authors make an attempt to identify the characteristics of labour force participation of immigrants and the main reasons for further development of labour market integration policy.
Keywords: labour market; migrant integration policy; the right to work for migrants; labour market effect from immigration